Characteristics of security risks of large industrial investments and their management principles - Frigyes Gubics (Belügyi Szemle)
Aim: Major construction and investment security is important if order to be done successfully. The aim of this article is to describe and analyses security relations of these kind of projects. Analyzing several part of security they affect the result of construction activities, risk assessment and risk mitigation, and of course to protect stake holders interests are the main directions of security activity. Secured environment also a base of achieve the expected results and activity of loss protection. Transparency, finalized workflows and tactics also can guarantee of a stable background during planning, implementation and later on final operation.